If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(x + 1) = 2(x + -1) + -16 Reorder the terms: 4x + -3(1 + x) = 2(x + -1) + -16 4x + (1 * -3 + x * -3) = 2(x + -1) + -16 4x + (-3 + -3x) = 2(x + -1) + -16 Reorder the terms: -3 + 4x + -3x = 2(x + -1) + -16 Combine like terms: 4x + -3x = 1x -3 + 1x = 2(x + -1) + -16 Reorder the terms: -3 + 1x = 2(-1 + x) + -16 -3 + 1x = (-1 * 2 + x * 2) + -16 -3 + 1x = (-2 + 2x) + -16 Reorder the terms: -3 + 1x = -2 + -16 + 2x Combine like terms: -2 + -16 = -18 -3 + 1x = -18 + 2x Solving -3 + 1x = -18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 1x + -2x = -18 + 2x + -2x Combine like terms: 1x + -2x = -1x -3 + -1x = -18 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + -1x = -18 + 0 -3 + -1x = -18 Add '3' to each side of the equation. -3 + 3 + -1x = -18 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -18 + 3 -1x = -18 + 3 Combine like terms: -18 + 3 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15
| 4y-x=12 | | 3y+20=5 | | 2(y-3x)=16-12x | | 11=44x-11y | | 8u+21=45 | | (X-4)=3x+2 | | 3-5x+9=25 | | f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 | | 48/165 | | 1/3(9x-12)=1/4(16x-12) | | 2x-5=3x-16 | | X/22=15/33 | | x+(x+1)+(x+2)=(x+3)+100 | | x+(x+1)+(x+2)=100 | | x-4=-x+6 | | 12/x=3/10 | | 3(7+10)+4(7+20)+5(7)=185-3(7) | | 2/6=6/x |